Kaat Van Doren : waiting for: GOLDEN HOUR - Doren, Kaat van; Beheydt, Tamara; Kolenberg, Katrien (Duffel : Stockmans Art Books, 2021)
Daylight. Nothing is more ubiquitous and yet many an artist has cursed under their breath in the search for a way to capture it. Indeed, which artist has not been fascinated by a unique shaft of light, a certain glow of the sun, or the shadows cast by some particular object? It is the ambition of scientists to study light, to explain it and make it measurable. It is a primordial instinct of visual artists to follow and capture light and its beauty. Although, as an artist, Van Doren is not loyal to any particular medium, carrier or material, she is constant in her search for light. Over the years, in works that the artist groups under the banner of 'Waiting for, Accidents of Nature', she has been occupied with painting the shadows that light leaves on her canvas. On other occasions she has made use of drawing materials and photographic techniques to capture 'found' shadows, such as those of a tree's leaves. She invites nature itself to interact, such as in her cyanotypes, where, facilitated by a light-sensitive emulsion, the sunlight leaves a blue impression on the canvas. This gives rise to images that are literally touched by nature. These works, as abstract visualisations of time created en plein air, possess certain impressionistic qualities. Sometimes she also amplifies the power of shadows, by cutting out or perforating their contours. Holes in the shape of the shadow or perforations that let the light through: in this way, Van Doren experiments with ways of influencing, shaping or containing natural light.
kunstcatalogus
Keywords: Doren, Kaat van; Sunlight in art